Anatomy of Influence: The Decisive Effect of Northrop Frye’s Anatomy of Criticism on James Reaney’s Donnellys Trilogy, as Directed by Keith Turnbull - Loretto, Teri R. (Université d'Ottawa / University of Ottawa, 2012)
Best known for his Donnellys Trilogy, Canadian playwright James Reaney completed his PHD under Northrop Frye. Frye’s thought and worldview are at the centre of these plays and although Reaney based his writing on a local legend from his childhood, it is undeniably grounded in Frye’s work, Anatomy of Criticism. Frye’s influence on Reaney becomes clear when Reaney’s trilogy is examined through the lens of Frye’s Anatomy. The plays manifest Frye’s structures concretely in space and time using props, setting, music, the spoken word and movement. An examination of the rehearsal hall methods of director Keith Turnbull reveals that Frye’s influence also extended to the actors’ preparation and the collective creation process that was critical to the resulting performances. Reviews and critiques, interviews with participants and an analysis of the trilogy in the context of Anatomy of Criticism give a greater understanding of the mechanics of the work and the resulting performances. In this study, elements of the plays are presented and discussed within the context of or with reference to Frye’s literary theory, making clear how the understanding of one contributes to the comprehension of the other. The relationship between a literary theory and live performance is here a powerful tool to understanding these theatrical works. This research establishes that it was also significant for the creation of one of Canada’s most pivotal dramatic works.